Digitalisasi Artefak Subak: Transformasi Mekanis Tenggala melalui Animasi Prosedural di Water Museum Mandala Mathika - Gede Agus Prayoga; I Putu Gede Suyoga; Ramanda Dimas Surya Dinata (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
The cognitive gap between the younger generation and agricultural heritage in museums is often caused by the static nature of artifacts and the limitations of informational media in explaining complex mechanical logic. This research aims to design a 3D educational animation titled